Muslim consumers' purchase intention of halal food in spain: The moderating effect of religious involvement / Mahir Pradana, Rubén Huertas-García and Frederic Marimon - Pradana, Mahir; Rubén, Huertas-García; Marimon, Frederic (UiTM Cawangan Johor, 2019)
There have been several research articles focusing on purchase intention of halal food product, but still a few focuses on the perspective of Spanish Muslim consumers. This study aims to observe society' purchase intention on halal food product in Spain. 500 respondents answered the questionnaire developed from the conceptual framework. Structural equation modeling is used to assess the fit of research framework with the help of SmartPLS version 3 software. The findings show that religious involvement's effect on purchase intention may vary. Meanwhile, purchase intention of halal product is determined by presumed influence and moderating effect of attitude towards halal product.